Applied Optimal Control of Spacecraft Simulator Subject to Failures of Reaction Wheels - Jamshidi, Somayeh; Mirzaei, Mehdi; Malekzadeh, Maryam (Arabian journal for science and engineering (2011), 2024)
In this paper, an optimal nonlinear attitude controller is designed and implemented as hardware in the loop for a spacecraft simulator under various failures of reaction wheels. The proposed controller is developed in the closed form based on predicting the nonlinear continuous responses of spacecraft simulator. The special case of the controller when all uncertainties are ignored leads to feedback linearization. However, the stability of the controller in the presence of parametric uncertainties and unmodeled dynamics of the platform is analyzed, and the effect of the prediction time on the boundedness of system responses is presented. A redundant reaction wheel is located in the platform to compensate for failures of three main reaction wheels. How to distribute torque between healthy wheels under different types of failure including stuck and oscillatory failures is addressed and experimentally implemented. The laboratory results that are consistent with computer simulations show the accuracy and validity of the designed controller. It is seen that the spacecraft attitude converges in a limited time in the presence of system uncertainties and actuator failures.